2021
DOI: 10.1007/s40123-020-00323-0
|View full text |Cite
|
Sign up to set email alerts
|

Are Current Methods of Measuring Dark Adaptation Effective in Detecting the Onset and Progression of Age-Related Macular Degeneration? A Systematic Literature Review

Abstract: Introduction: Dark adaptation (DA) has been proposed as a possible functional biomarker for age-related macular degeneration (AMD). In this systematic review we aim to evaluate current methodology used to assess DA in people with AMD, the evidence of precision in detecting the onset and progression of AMD, and the relationship between DA and other functional and structural measures. Methods: MEDLINE, EMBASE, CINAHL, AMED, PsycINFO, PsycARTICLES were searched for studies published between January 2006 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
(418 reference statements)
0
5
0
Order By: Relevance
“…Elsewhere in the literature, there is overwhelming evidence of an association between impaired dark adaptation and AMD but the studies of the discrimination performance of RIT in separating people with different levels of AMD are limited. 10 Good levels of test-retest variability of the S-MAIA (both mesopic and scotopic conditions) have been previously reported using CoR metrics. For example, Welker et al (2018) reported CoR of 4.4 dB (mesopic) and 4.52 dB (scotopic) for pointwise sensitivity in a small number ( n = 23) of volunteers with iAMD.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Elsewhere in the literature, there is overwhelming evidence of an association between impaired dark adaptation and AMD but the studies of the discrimination performance of RIT in separating people with different levels of AMD are limited. 10 Good levels of test-retest variability of the S-MAIA (both mesopic and scotopic conditions) have been previously reported using CoR metrics. For example, Welker et al (2018) reported CoR of 4.4 dB (mesopic) and 4.52 dB (scotopic) for pointwise sensitivity in a small number ( n = 23) of volunteers with iAMD.…”
Section: Discussionmentioning
confidence: 71%
“…Assessment of test-retest variability for a device in small numbers of visually healthy people is inadequate. For instance, in a recent systematic review of the measurement of dark adaptation, with a focus on the AdaptDx device, 10 we found only one study to have adequately attempted to assess test-retest variability and this did not specify the disease status of the cohort recruited. 11 Better reports on the topic for measurements from S-MAIA exist.…”
Section: Introductionmentioning
confidence: 99%
“…There are many excellent resources by eminent authors that describe visual changes during dark and light adaptation [ 6 ] visual function and functional vision in presence of aging and early AMD [ 7 , 8 , 9 ]. A recent literature review focuses on the effectiveness of current DA measuring methods in detecting onset and progression of AMD [ 10 ], however a specific focus on clinical aspects of DA measurement and its significance to furthering our understanding of AMD integrating physiological aspects of DA, AMD pathophysiology, significance of DA as a functional biomarker, different methodologies and correlation of DA with patient reported outcome measures (PROMs), has been an important area of development. Given the wealth of research studies in recent years specifically related to DA and AMD, this review article is timely.…”
Section: Introductionmentioning
confidence: 99%
“…OCT has many advantages over CFP, such as better differentiating between structural abnormalities such as SDDs 21 in three-dimensions 26 . Our recent systematic literature review 27 highlighted OCTbased studies that have revealed new relationships between AMD macular anatomy (such as SDDs) and RMDA 6,8,25,28,29 . However, the sample sizes of the SDD cohorts (n=<20) 6,8,25 have been small and few included age-adjusted control groups.…”
Section: Introductionmentioning
confidence: 99%